PERANCANGAN SCISSOR LIFT SEBAGAI ALAT PENGANGKAT MOBIL SOEDIRMAN II - Muhammad Fadhlan Mursyidan (2022)
At UPN Veteran Jakarta, Faculty of Mechanical Engineering, during the assembly and maintenance process, Sudirman II's car experienced problems because the car was still on the ground or below, which made sometimes Sudirman II's car was lifted together by 6-8 people. From these problems, a Scissor Lift was designed to make it easier for the UPN Veteran Jakarta team in the assembly and maintenance process for Sudirman II's car. The design of the Scissor Lift is carried out in order to be able to lift a maximum load of 250 Kg to a height of 120 cm from the ground surface by calculating the forces that occur in the Scissor Lift by finding the hydraulic cylinder force required at the lowest and highest positions and analyzing the strength to determine the value. stress, deformation and safety factor. After calculation and analysis, it is known that the hydraulic cylinder force needed to support the design when the Scissor Lift is in the lowest and highest positions is 23756 N and 13141 N. And from all Scissor Lift parts that have been analyzed, the results of the minimum safety factor on the upper stem parts are worth of 1.5. These results indicate that the part still meets the standards and is safe to use. The design of the Scissor Lift is very possible to be supported by the weight sensor feature so that it can provide information if the load exceeds 250 Kg in the future.